From prenatal detection to postnatal evaluation: a retrospective observational ultrasound study of patent urachus with allantoic cyst - Lanxin Du; Xinyue Jing; Ying Tang; Houqing Pang; Xiayu Yan; Lu Ye; Hong Luo (BMC Pregnancy and Childbirth)
Abstract Background Patent urachus with allantoic cyst (PUAC) is a rare abnormal embryonic development characterized by a prenatal umbilical mass and postpartum bladder prolapse. The current literature is mainly case reports, and there is a lack of consecutively observational studies of this disease. Objectives This study aims to investigate the impact of the disease on fetal development through a retrospective analysis of prenatal ultrasound progression, pregnancy outcomes, and postnatal follow-up, thereby establishing an evidence-based foundation for prenatal clinical recommendations. Materials and methods We performed a retrospective analysis of cases identified between January 2012 and December 2022, in which first-trimester sonographic screening demonstrated an umbilical cystic mass with anechoic tubular connections to the fetal bladder. Detailed clinical information about the pregnant individuals, prenatal ultrasonographic changes, genetic outcomes, abdominal appearance of newborns and stillbirths, comorbidities, surgical repair and neonatal follow-up were meticulously recorded and analyzed. Results Nine cases met the ultrasound inclusion criteria. Except for one lost to follow-up in second trimester, the remaining eight cases were confirmed as PUAC after birth or induction. Serial ultrasonography demonstrated progressive enlargement of the allantoic cysts with advancing gestational age, culminating in rupture during the second or third trimester and subsequent umbilical mass formation. In postnatal analysis, prolapsed bladder was identified as the predominant component of the umbilical mass, with intestinal involvement observed in some cases. Transient or persistent dilatation of the renal pelvis occurred in over 50% of the fetuses. During long-term follow-up, patients were observed to experience abdominal pain, urinary frequency, and urinary tract infections, with one case showing bilateral vesicoureteral reflux. Only one case showed abnormal genetic results, specifically a 17p12 duplication, which can lead to Charcot-Marie-Tooth syndrome Type 1 A (CMT1A). Conclusion This study highlights that isolated PUAC represents a fetal condition with a favorable prognosis. Dynamic prenatal ultrasound monitoring allows serial documentation of umbilical lesion progression, critically providing assistance for postpartum surgical intervention and prenatal counseling.